Use of free tissue transfer in head and neck cancer surgery and risk of overall and serious complication(s): An American College of Surgeons–National Surgical Quality Improvement Project analysis of free tissue transfer to the head and neck. Issue 4 (21st December 2016) - Cannady, Steven B.; Hatten, Kyle M.; Bur, Andres M.; Brant, Jason; Fischer, John P.; Newman, Jason G.; Chalian, Ara A.
ABSTRACT: Background: The purpose of this article was to assess the rates of head and neck free tissue transfer and variables available in the American College of Surgeons – National Surgical Quality Improvement Project (ACS–NSQIP) dataset to predict overall and serious complications. Methods: We conducted a data analysis from 2005 to 2014 on free tissue cases in the head and neck with descriptive and cross‐sectional analysis to examine correlation of NSQIP variables with complications ( p < .05). Results: Of 1643 flaps, 906 complications occurred, such as blood transfusion, return to the operating room, extended ventilator support, pneumonia, and superficial surgical site infection. Insulin‐dependent diabetes, operative time, age, white blood cell (WBC) count, and smoking correlated with overall complications. Five hundred one patients experienced 859 serious complications: return to the operating room, pneumonia, deep surgical site infection, sepsis, and unplanned intubation. Operative time, clean contaminated wound status, dirty wound classification, and history of congestive heart failure were predictive. Conclusion: Identification of risks for complications is an opportunity for improvement. Extended operative time consistently predicts for both overall and serious complications, suggesting long surgery within contaminated sites risks complication. © 2016 Wiley Periodicals, Inc. Head Neck 39: 702–707, 2017